Training-specific adaptation of multi-finger coordination - Shim, J. K.; Hsu, J.; Karol, S.; Kim, Y. S.; Hurley, B. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of the present study was to investigate the effects of finger Strength Training (ST) on multi-finger coordination as well as individual finger control, independence, and strength. Thirty-three healthy, young subjects were randomly assigned into four groups. Group 1 (G1) trained all fingers together, Group 2 (G2) trained individual fingers without restricting movements of the non-training fingers, and Group 3 (G3) trained individual fingers while restricting the movement of the non-training fingers. The control group (G0) did not undergo any training. All subjects in G1, G2, and G3 performed six sets of ten repetitions at 70% of their one repetition maximum for each sesson for six weeks, and there were three sessions of training per week. Identical experimental tests were conducted four times, biweekly, across the six-week training. Moment stabilizing multi-finger coordination increased only in G1, while force stabilizing coordination increased only in G3. Finger strength increased significantly in all training groups. Finger force control errors decreased significantly with ST for all the training groups. Finger independence also decreased significantly for all the training groups. We conclude that the neuromuscular adaptations to finger ST are specific to the training protocol being employed, yielding improvements in different types of multi-finger coordination (i.e., ST specificity for coordination), finger force control, finger strength and a decrease in finger independence. We suggest that ST protocol should be carefully designed for the improvement of specific coordination of multi-effector motor systems.